Care for children with cancer facing the COVID-19 pandemic: Integrative literature review (Research, Society and Development, 2021)
Integrative review has been an important tool for research in the area of ​​health knowledge as it allows the synthesis of research on a given subject. Numerous challenges to control the dissemination of COVID-19 affected the population's understanding of all the safety measures proposed by public health agencies, especially with regard to transmission. And, in this pandemic scenario, children are not spared, despite being less vulnerable to illness from this disease, however, they may have asymptomatic infection and the elimination of the virus in respiratory secretions and feces seems to be longer than in adults, which can contribute to the dissemination of COVID-19. Thus, this study aims to: Conduct an integrative literature review on the main care recommendations for children with cancer to reduce injuries and complications in the context of the COVID-19 pandemic. The research encompassed the search and selection of national and published in the period 2020 to 2021. The search for articles was performed in the PubMed, CINAHL and Scopus databases. The results of the analysis showed the main recommendations are aimed at minimizing the visit of these children to the hospital for return appointments or monitoring, being evident the use of telemedicine as the main resource in order to avoid contamination by the new coronavirus, monitoring by rapid tests for COVID-19 was also widely used, reducing the number of companions in the hospital and using protective equipment such as masks for professionals, patients and companions, some studies reported that chemotherapy treatments should be suspended, as well as elective cancer surgeries, until the risk of contamination was reduced, monitoring professionals in the oncology sectors for signs of infection by covid, online consultations and home monitoring were also mentioned strategies. It is concluded that the main recommendations involved protecting children who are already immunocompromised by the comorbidity that is cancer of COVID-19, and for this, several institutions that work with this audience exchanged knowledge and experience reports so that the others could continue as successful.